How Do We Prioritize the GHG Mitigation Options? : Development of a Marginal Abatement Cost Curve for the Building Sector in Armenia and Georgia - Timilsina, Govinda (World Bank, Washington, DC, 2016)
Armenia and Georgia are taking the climate change agenda seriously and contributing to efforts for mitigating global climate change through various ways, including preparation of low-carbon development strategies for their future economic growth. The improvement of energy efficiency is one of the key elements of the low-carbon development strategies. This study develops a methodology to estimate a marginal abatement cost curve for energy efficiency measures and applies it to the building sector in both countries. The study finds that among the various energy efficiency measures considered, the replacement of energy inefficient lightbulbs (incandescent lamps) with efficient lightbulbs is the most cost-effective measure in saving energy and reducing greenhouse gas emissions from the building sector. Most energy efficiency improvement options considered in the study would produce net economic benefits even if the value of reduced carbon is not taken into account.